Attitudes and decisions about sexual offenders: a comparison of laypersons and professionals - Jung, Sandy; Jamieson, Lisa; Buro, Karen; DeCesare, John (My University, 2012)
The current study examines the inherent biases about sexual offending held by 123 laypersons and 120 professionals (i.e. probation officers and therapists). In order to determine the extent of these biases, a series of brief newspaper articles were constructed to depict cases of sexual offenders. Each article comprised several combinations of key variables, including offender type, level of admission, and the presence of alcohol. Participants read a series of three fabricated articles and then completed a questionnaire regarding attitudes about the various offenders. The results indicate important differences between the lay and professional samples. Laypersons deemed sex offenders more favourably in terms of character, accountability, and risk for sexual recidivism. However, both groups showed some similar perceptions about sexual offending. Specifically, both groups evaluated child molesters more negatively than exhibitionists and in some cases, rapists. These findings highlight the need for continuing education for professionals in order to attenuate the effects of prejudicial attitudes.
Keywords: attitudes; professionals; sex offenders; perceptions; denial; laypersons